Economic life in Khorezm in the 18th - 19th centuries: on the example of the rule of the Kungirats (Texas Journal of Philology, Culture and History, 2026)
In the 18th - 19th centuries, economic life in Khorezm developed further. During this period, the internal and external trade relations of the Khiva Khanate intensified, and diplomatic relations with many countries began to be established. This article examines the development of economic life in the Khiva Khanate during the period of the Kungirats.